Maṣlaḥah-Based Fatwa Formulation: The Indonesian Ulema Council’s Rejection of Mut'ah Marriage in the Context of Women's Rights Protection - Alwi, Mujahid (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
This study aims to examine the protection of women's rights in the fatwa issued by the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) concerning mut'ah marriage, through the lens of the Maṣlaḥah (public interest) principle. The research adopts a qualitative library-based approach, focusing on textual analysis of primary sources such as the Qur’an, classical and contemporary Islamic legal literature, and scholarly articles. Using the Maṣlaḥah framework, the study analyzes the MUI's legal reasoning and its implications for safeguarding women’s welfare. The findings reveal that the MUI fatwa rejects the practice of mut'ah marriage on the grounds that it undermines legal certainty and moral integrity, especially for women, and contradicts the objectives of Islamic law in ensuring justice, protection, and public benefit. The MUI asserts that marriage must comply with both Islamic teachings and national legal standards, including formal registration, to ensure women’s legal protection. This research contributes originality by highlighting how Maṣlaḥah serves not only as a legal tool but also as an ethical framework in contemporary fatwa formulation. The implications of this study suggest that integrating Maṣlaḥah into fatwa development can reinforce the protection of vulnerable groups, such as women, and align religious rulings with broader societal interests.